Transcription Factors and Their Roles in Signal Transduction in Plants under Abiotic Stresses - Lan Thi Hoang, Xuan; Ngoc Hai Nhi, Du; Binh Anh Thu, Nguyen; Phuong Thao, Nguyen; Phan Tran, Lam-Son (Current Genomics, 2017)
In agricultural production, abiotic stresses are known as the main disturbance leading to negative impacts on crop performance. Research on elucidating plant defense mechanisms against the stresses at molecular level has been addressed for years in order to identify the major contributors in boosting the plant tolerance ability. From literature, numerous genes from different species, and from both functional and regulatory gene categories, have been suggested to be on the list of potential candidates for genetic engineering. Noticeably, enhancement of plant stress tolerance by manipulating expression of Transcription Factors (TFs) encoding genes has emerged as a popular approach since most of them are early stress-responsive genes and control the expression of a set of downstream target genes. Consequently, there is a higher chance to generate novel cultivars with better tolerance to either single or multiple stresses. Perhaps, the difficult task when deploying this approach is selecting appropriate gene(s) for manipulation. In this review, on the basis of the current findings from molecular and post-genomic studies, our interest is to highlight the current understanding of the roles of TFs in signal transduction and mediating plant responses towards abiotic stressors. Furthermore, interactions among TFs within the stress-responsive network will be discussed. The last section will be reserved for discussing the potential applications of TFs for stress tolerance improvement in plants.
Keywords: Crop improvement